COMMUNITY EMPOWERMENT THROUGH POPULATION CENTERED HEALTH NURSING CARE IN THE PREVENTION AND MANAGEMENT OF TRAUMA IN THE GROUP OF FARMERS OF THE INSAN MULIA LUMAJANG FOUNDATION - Arista Maisyaroh; Eko Prasetya Widianto; Syaifuddin Kurnianto; Rizeki Dwi Fibriansari (UPT Penerbitan Universitas Jember, 2022)
The problem identified from the livestock group that is part of the Insan Mulia Lumajang Foundation is that the farmer's level of knowledge is still low on the risk of trauma that can occur as a result of his work. This group of breeders still considers it normal if there is trauma while working and the management is also still not right, causing infectious complications due to incorrectly taking initial actions to treat wounds. (jika ada). The solution offered is to increase the ability of breeders to reduce the risk of trauma due to their work by identifying the cause of the trauma and anticipating and training the right initial management to reduce the risk of infection. Problem solving from partners is carried out in a community service scheme with stages of providing health education about early detection of trauma events due to workers in livestock and agricultural areas, management to reduce trauma due to sharp objects, and training in carrying out appropriate initial management actions in handling trauma wounds in livestock and agricultural areas. The result of this community service program is that farmers can reduce the incidence of trauma due to work and can carry out initial management of wound management independently so as to reduce the risk of infection. Keywords: management trauma ,occupational diseases, farmer